1996
DOI: 10.1128/mcb.16.5.2453
|View full text |Cite
|
Sign up to set email alerts
|

Spi-1/PU.1 Transgenic Mice Develop Multistep Erythroleukemias

Abstract: Insertional mutagenesis of the spi-1 gene is associated with the emergence of malignant proerythroblasts during Friend virus-induced acute erythroleukemia. To determine the role of spi-1/PU.1 in the genesis of leukemia, we generated spi-1 transgenic mice. In one founder line the transgene was overexpressed as an unexpected-size transcript in various mouse tissues. Homozygous transgenic animals gave rise to live-born offspring, but 50% of the animals developed a multistep erythroleukemia within 1.5 to 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
196
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(206 citation statements)
references
References 54 publications
(55 reference statements)
8
196
0
2
Order By: Relevance
“…In the HS2 step, proerythroblast proliferation was growth factor-independent and these cells were also tumorigenic in vivo (Moreau-Gachelin et al, 1996). F-MuLV (B3) infection did not change the timing of the disease progression or the properties of the proliferating proerythroblasts which were Epo-independent in vitro and tumorigenic in vivo.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In the HS2 step, proerythroblast proliferation was growth factor-independent and these cells were also tumorigenic in vivo (Moreau-Gachelin et al, 1996). F-MuLV (B3) infection did not change the timing of the disease progression or the properties of the proliferating proerythroblasts which were Epo-independent in vitro and tumorigenic in vivo.…”
Section: Resultsmentioning
confidence: 91%
“…It was previously reported that B3 had a low virulence and induced various types of leukemias only after more than 10 months (Sitbon et al, 1986). Among the 58 B3-infected spi-1 transgenic mice, 28 developed the hepatosplenomegaly (HS1) and anemia characteristics of the transgenic disease (Moreau-Gachelin et al, 1996). The incidence of the disease (48%) was similar to that observed in uninfected transgenic mice, whereas the mean latency of outgrowth (3.0+1.5 months) appeared slightly shorter than in uninfected animals (3.6+1.5 months).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations